Effects of Various Weed Infestations on Soybean Yield and Soil Moisture Utilization - Moolani, M.K (Journal of Soil and Water Conservation, 2022)
Available soil-moisture is a ma- jor factor limiting plant growth under many conditions of crop pro- duction. Many of the observed crop yield reductions caused by weed infestations have resulted from the competitions of weeds for available soil moisture (Blackman and Tem- pleman, 1938; Staniforth and We- ber, 1956). Competition for water, often may be modified by the effects of competition for soil nutrients and the shading effects of plants (Pavly- chenko and Harrington, 1934). Soybean yield reductions due to competition with foxtail, Setaria faberii Hermm., were small when soil-moisture was adequate over the whole season (Staniforth, 1958). Corn yield reductions of 560/0 and 51 0/0 respectively for dry seasons of 1953 and 1955 and 33% reductions in normal weather of 1952 and 1954 were reported by Vengris et al (1955) thus showing more depres- sing effects of weeds in dry rather than in wet seasons.